Topical retapamulin in the management of infected traumatic skin lesions - Ribhi Shawar; Nicole Scangarella-Oman; MaryBeth Dalessandro; John Breton; Monique Twynholm; et al (Dove Medical Press, 2008)
Ribhi Shawar1, Nicole Scangarella-Oman1, MaryBeth Dalessandro2, John Breton2, Monique Twynholm3, Gang Li4, Harmony Garges51Infectious Disease Center for Excellence in Drug Discovery, GlaxoSmithKline, Collegeville, PA, USA; 2Anti-infectives Medicine Development Center, GlaxoSmithKline, Collegeville, PA, USA; 3Infectious Diseases Medicine Development Centre Europe, GlaxoSmithKline, Greenford, Middlesex, UK; 4MDC BDS – Infectious Disease, GlaxoSmithKline, Collegeville, PA, USA; 5Anti-infectives Medicine Development Center, GlaxoSmithKline, Research Triangle Park, NC, USAAbstract: Retapamulin is a novel semisynthetic pleuromutilin antibiotic specifically designed for use as a topical agent. The unique mode of action by which retapamulin selectively inhibits bacterial protein synthesis differentiates it from other nonpleuromutilin antibacterial agents that target the ribosome or ribosomal factors, minimizing the potential for target-specific cross-resistance with other antibacterial classes in current use. In vitro studies show that retapamulin has high potency against the Gram-positive bacteria (Staphylococcus aureus, Streptococcus pyogenes, and coagulase-negative staphylococci) commonly found in skin and skin-structure infections (SSSIs), including S. aureus strains with resistance to agents such as macrolides, fusidic acid, or mupirocin, and other less common organisms associated with SSSIs, anaerobes, and common respiratory tract pathogens. Clinical studies have shown that twice-daily topical retapamulin for 5 days is comparable to 10 days of oral cephalexin in the treatment of secondarily infected traumatic lesions. A 1% concentration of retapamulin ointment has been approved for clinical use as an easily applied treatment with a short, convenient dosing regimen for impetigo. Given the novel mode of action, low potential for cross-resistance with established antibacterial agents, and high in vitro potency against many bacterial pathogens commonly recovered from SSSIs, retapamulin is a valuable enhancement over existing therapeutic options.Keywords: retapamulin, traumatic skin lesions, topical antibiotic, skin infections, Staphylococcus aureus